Environmentally Benign Fouling-Resistant Marine Coatings: A Review. Issue 5 (24th March 2019) - Pradhan, Sukanya; Kumar, Sudheer; Mohanty, Smita; Nayak, Sanjay K.
ABSTRACT: The undesirable accumulation of marine organisms on any surfaces immersed in seawater is termed as marine fouling. This natural phenomenon contributes a major economic concern for marine industries, e.g. for ships, vessels, oil, wind-turbine sea-platforms, pipelines, water valves and filters by limiting the performances of the devices and materials. In the last decades, several efforts have been employed in the development of efficient antifouling (AF) coatings by following the recent trend in materials science. The current review presents the research and development made in AF strategies for coatings based on two main approaches, detachment of biofoulants or preventing biofoulants attachment. Graphical Abstract: GRAPHICAL ABSTRACT